Omics Approaches for Understanding Biogenesis, Composition and Functions of Fungal Extracellular Vesicles - Zamith-Miranda, Daniel; Peres da Silva, Roberta; Couvillion, Sneha P.; Bredeweg, Erin L.; Burnet, Meagan C.; Coelho, Carolina; Camacho, Emma; Nimrichter, Leonardo; Puccia, Rosana; Almeida, Igor C.; Casadevall, Arturo; Rodrigues, Marcio L.; et al. (Frontiers in Genetics, 2021)
Extracellular vesicles (EVs) are lipid bilayer structures released by organisms from all kingdoms of life. The diverse biogenesis pathways of EVs result in a wide variety of physical properties and functions across different organisms. Fungal EVs were first described in 2007 and different omics approaches have been fundamental to understand their composition, biogenesis and function. In this review, we discuss the role of omics in elucidating fungal EV biology. Transcriptomics, proteomics, metabolomics and lipidomics have each enabled the molecular characterization of fungal EVs, providing evidence that these structures serve a wide array of functions, ranging from key carriers of cell wall biosynthetic machinery to virulence factors. Omics in combination with genetic approaches have been instrumental in determining both biogenesis and cargo loading into EVs. We also discuss how omics technologies are being employed to elucidate the role of EVs in antifungal resistance, disease biomarkers, and their potential use as vaccines. Finally, we review recent advances in analytical technology and multi-omic integration tools, which will help to address key knowledge gaps in EV biology and translate basic research information into urgently needed clinical applications such as diagnostics, and immuno- and chemotherapies to fungal infections.